Implementing ISAK 35 in Non-profit Organizations: A Case Study of Yayasan Pendidikan Nurussholih - Hasibuan, Jihan Isnaini; Syafina, Laylan; Syarvina, Wahyu (Yayasan Sinergi Kawula Muda, 2024)
This paper investigates the implementation of ISAK 35 as a framework for financial reporting in non-profit organizations, focusing on Yayasan Pendidikan Nurussholih. The study addresses the significant challenges non-profits encounter in adhering to new accounting standards. It examines why the monthly financial reports of Yayasan Pendidikan Nurussholih do not comply with ISAK 35 and identifies specific implementation hurdles. This research sheds light on the unique difficulties this non-profit organization faces in adopting ISAK 35, an area underexplored in prior literature. A qualitative case study methodology was employed, utilizing both primary (interviews with key informants) and secondary data (bank records, historical documents). Findings reveal that while Yayasan Pendidikan Nurussholih utilizes BOS funds for monthly reporting, it struggles with comprehending and implementing ISAK 35 due to financial constraints, complex bookkeeping, and limited technology use. Non-compliance with ISAK 35 may undermine donor confidence in the foundation's financial disclosures. The study concludes that additional support and resources are essential for non-profits to achieve full compliance with ISAK 35. It emphasizes the necessity of tailored solutions to help non-profit organizations overcome these specific challenges and improve their financial reporting practices.